Highly clean polyester and its preparation method and application
Patent Information
- Application Number
- CN202511817356.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-04
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2045-12-04
AI Technical Summary
[0004]然而,目前的聚对苯二甲酸乙二醇酯主要应用在服饰或瓶体等领域,如果要作为医用材料,需要对其杂质含量和物性参数进行调控,以具备足够的力学性能、人体内的物理化学稳定性以及安全性等,特别是当前的聚对苯二甲酸乙二醇酯的特性黏度按照常规工艺、常规设备很难做高,对其性能的负面影响较大,同时还含有较高量的二甘醇(HO-CH2CH2-O-CH2CH2-OH,简称DEG)及其参与反应生成的醚键官能团、乙醛以及金属等杂质,2,2'-氧代二乙醇参与生成的醚键官能团容易在体内发生降解,可能释放小分子杂质,引发组织刺激或炎症,同时降解后的材料的力学稳定性也无法满足医用要求,力学性能的衰减会导致植入器械(如人工血管、缝合线)提前失效;此外,金属杂质尤其是对人体不友好的重金属容易带来负面影响,进而导致常规的聚对苯二甲酸乙二醇酯难以直接应用在医疗尤其是与人体内部相关的材料中
本发明基于常规的聚对苯二甲酸乙二醇酯存在的特性粘度不足、杂质含量高等缺陷,创新地提供了一种改进的聚酯的制备方法,该方法基于本发明的大量实验研究,在制备过程中,先从小分子原料制备纯净的小分子对苯二甲酸双羟乙酯,进一步使其发生歧化,完成分子量分布的调整,同时再结合对苯二甲酸二甲酯与乙二醇在常压条件下混合反应,进一步实现聚酯前驱体的多种形态生成,例如可生成对苯二甲酸双羟乙酯以及低聚体诸如二聚体和三聚体等,也即本发明通过控制乙二醇在不同的条件下分步完成聚酯的前驱体制备,当将它们的反应产物混合进行缩聚时,不同的聚酯前驱体和不同聚合度的低聚体可以迅速完成扩链扩增,避免单一前驱体可能导致的当分子量上升到一定程度后难以再上升的问题,最后通过热处理实现固相增粘和进一步除杂。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of polyester production technology, and more particularly to medical polyester materials, specifically to a high-purity polyester, its preparation method, and its application. Background Technology
[0002] In recent years, with the rapid development of medical and biotechnology, the demand for medical materials has been increasing year by year. The requirements for materials in the medical field are very strict. Materials are required to have stable physicochemical properties, be easy to process, have no toxic side effects, not contaminate packaging materials, and also have good performance, lightweight and durable properties.
[0003] Polyethylene terephthalate (PET) possesses relatively excellent biocompatibility, relatively stable physicochemical properties, processability, and sterilization compatibility, making it one of the preferred polymer materials for the medical field. Its biocompatibility helps meet the core safety requirements of medical materials. For example, it holds promise for applications in cardiovascular fields such as PET artificial blood vessels, heart valve pads, and sutures for soft tissue repair.
[0004] However, current polyethylene terephthalate (PET) is mainly used in clothing and bottle manufacturing. If it is to be used as a medical material, its impurity content and physical properties need to be controlled to ensure sufficient mechanical properties, physicochemical stability in the human body, and safety. In particular, the intrinsic viscosity of current PET is difficult to achieve with conventional processes and equipment, significantly impacting its performance. It also contains high levels of diethylene glycol (HO-CH2CH2-O-CH2CH2-OH, DEG) and its ether functional groups generated during the reaction, acetaldehyde, and metallic impurities. The ether functional groups generated by 2,2'-oxodiethanol are prone to degradation in vivo, potentially releasing small molecule impurities that can cause tissue irritation or inflammation. Furthermore, the mechanical stability of the degraded material cannot meet medical requirements, and the decline in mechanical properties can lead to premature failure of implanted devices (such as artificial blood vessels and sutures). In addition, metallic impurities, especially heavy metals that are harmful to the human body, can have negative effects, making it difficult to directly apply conventional PET in medical applications, especially in materials related to the human body.
[0005] It should be noted that the information disclosed in the background section above is only for understanding the background of this application. Therefore, the background section of this invention may include background information about the problems or environment of this invention, and is not necessarily a description of the prior art. Thus, the content included in the background section does not constitute an admission of the prior art by the applicant. Summary of the Invention
[0006] The purpose of this invention is to overcome one or more shortcomings in the prior art and provide an improved method for preparing polyester. This method can obtain polyester materials with high purity, especially with significant inhibition of specific impurities such as DEG and acetaldehyde. It also has excellent and suitable intrinsic viscosity, which is beneficial for the application of polyester materials in medical materials.
[0007] The present invention also provides a high-purity polyester prepared by the above method and its application in the preparation of medical materials.
[0008] To achieve the above objectives, the present invention employs the following technical solution: A method for preparing a polyester, the method comprising: (1) Terephthalic acid and ethylene glycol undergo an esterification reaction. After the reaction is completed, the mixture is separated and purified to obtain purified dihydroxyethyl terephthalate. The purified dihydroxyethyl terephthalate was subjected to a disproportionation reaction with ethylene glycol to obtain the first reaction mixture; Dimethyl terephthalate and ethylene glycol are mixed and reacted under normal pressure. After the reaction is completed, a second reaction mixture is obtained. (2) The first reaction mixture and the second reaction mixture are subjected to polycondensation reaction in the presence of a polycondensation catalyst. After the reaction is completed, the polycondensation product is heat-treated under vacuum to obtain polyester.
[0009] In some embodiments of the present invention, in the esterification reaction, the molar amount of ethylene glycol added is more than twice the molar amount of terephthalic acid added. Further, the molar amount of ethylene glycol added is 2-6 times the molar amount of terephthalic acid added, for example, 2 times, 2.5 times, 3.0 times, 3.5 times, 4.0 times, 4.5 times, 5.0 times, 5.5 times, 6.0 times, etc. Practice has shown that excess ethylene glycol promotes the formation of diethyl terephthalate.
[0010] In some embodiments of the present invention, in the mixing reaction, the molar amount of ethylene glycol added is 1.1-2 times the molar amount of dimethyl terephthalate added, for example, it can be 1.1 times, 1.2 times, 1.3 times, 1.4 times, 1.5 times, 1.6 times, 1.7 times, 1.8 times, 1.9 times, 2.0 times, etc.
[0011] In this invention, during the mixing reaction, not only does transesterification occur, but oligomers are also generated, such as dimers or trimers. In particular, by controlling the amount of added molar amount, the etherification of ethylene glycol (i.e., the generation of DEG and acetaldehyde) can be reduced when obtaining a mixture with a wider molecular weight distribution.
[0012] In some embodiments of the present invention, the esterification reaction is controlled at a temperature of 230-260°C and a pressure of 0.005-0.32 MPa. According to the present invention, the pressure during the esterification reaction is primarily generated by the water vapor and ethylene glycol vapor produced during the reaction. When a large amount of vapor is generated, the pressure inside the reaction vessel, such as a reactor, will increase (if it exceeds a preset value, pressure relief can be implemented to maintain it below the preset value, and ethylene glycol will reflux and continue to participate in the reaction). When the amount of water produced begins to decrease in the later stages of the reaction, the pressure inside the reaction vessel will gradually decrease. Therefore, in the actual esterification process, it is only necessary to control the maximum pressure to be below the preset value.
[0013] In some embodiments of the present invention, the method for preparing the purified dihydroxyethyl terephthalate includes: Terephthalic acid and ethylene glycol undergo an esterification reaction. The reaction ends when the amount of water discharged reaches more than 95% of the theoretically calculated value. Then, under a protective atmosphere, the reactants are discharged into a container, cooled and crystallized, and filtered to obtain crude dihydroxyethyl terephthalate. The crude diethyl terephthalate was dissolved in a solvent under heating conditions, activated carbon was added, and the mixture was filtered. The filtrate was cooled and crystallized, then filtered again. This process was selectively repeated multiple times to obtain purified diethyl terephthalate.
[0014] Furthermore, the solvent is one or a combination selected from water, methanol, ethanol, n-propanol, formic acid, and acetic acid.
[0015] In some embodiments of the present invention, the crude diethyl terephthalate is completely dissolved in a solvent by heating. Further, the heating temperature can be 30-80°C, etc., and can be specifically determined according to the solvent.
[0016] Furthermore, the mass of activated carbon added is 0.5%-5% of the mass of crude bis(hydroxyethyl) terephthalate added.
[0017] Furthermore, the crystallization temperature of the cooling crystallization is 1-10℃, and the cooling rate is 0.1-1℃ / min.
[0018] In this invention, purification can remove impurities such as DEG and acetaldehyde that may be generated during the esterification reaction in advance. At the same time, it can further remove impurities such as heavy metals that may be carried in the raw materials, which is beneficial for the subsequent preparation of high-purity polyester.
[0019] In some embodiments of the present invention, in the disproportionation reaction, the molar ratio of the purified dihydroxyethyl terephthalate to the ethylene glycol is 1:0.5-5, for example, it can be 1:0.5, 1:0.8, 1:1, 1:1.5, 1:1.8, 1:2.0, 1:2.5, 1:2.8, 1:3.0, 1:3.2, 1:3.5, 1:4.0, 1:4.2, 1:4.5, 1:5.0, etc.
[0020] In some embodiments of the present invention, the disproportionation reaction is controlled to occur under a protective atmosphere at 150-180°C.
[0021] In this invention, by adding an additional disproportionation reaction step, the uniformity of the molecular structure can be broken, and oligomers with uneven degree of polymerization can be generated, providing prepolymers for subsequent polycondensation reactions and avoiding the problem that the molecular weight is difficult to increase in the later conventional polycondensation reaction.
[0022] In some embodiments of the present invention, the mixing reaction is controlled to proceed in the presence of a catalyst. Further, the catalyst is a combination of one, two, or more selected from alkali metal acetates and transition metal acetates; Furthermore, the catalyst is composed of alkali metal acetate and transition metal acetate. Even further, the mass ratio of the alkali metal acetate to the transition metal acetate is 1:1.2-1.6.
[0023] In some embodiments of the present invention, the mixing reaction is controlled to proceed in the presence of a catalyst, and further, the mass of the catalyst is one to one-thousandth of the mass of the dimethyl terephthalate.
[0024] In some embodiments of the present invention, the mixing reaction is controlled to be carried out at 180-240°C.
[0025] In some embodiments of the present invention, the reaction endpoint of the mixed reaction is controlled to be that the amount of methanol produced reaches more than 90% of the theoretically calculated value.
[0026] In some embodiments of the present invention, the preparation method further includes: adjusting the feeding ratio of the first reaction mixture and the second reaction mixture by controlling the feeding amount of the purified diethyl terephthalate and the feeding amount of dimethyl terephthalate. Further, based on a total feeding amount of 100% for both dimethyl terephthalate and the purified diethyl terephthalate, the dimethyl terephthalate accounts for 30%-70%, and the purified diethyl terephthalate accounts for 30%-70%. Even further, based on a total feeding amount of 100% for both dimethyl terephthalate and the purified diethyl terephthalate, the dimethyl terephthalate accounts for 50%-70%, and the purified diethyl terephthalate accounts for 30%-50%.
[0027] According to certain specific aspects of the present invention, based on a total feed amount of 100% for the dimethyl terephthalate and the purified diethyl terephthalate, the dimethyl terephthalate accounts for 55%-65%, and the purified diethyl terephthalate accounts for 35%-45%.
[0028] In some embodiments of the present invention, the polycondensation catalyst is a titanium catalyst, a germanium catalyst, or a combination of both.
[0029] Furthermore, the titanium catalyst comprises a titanate, and the germanium catalyst comprises organic germanium.
[0030] In some embodiments of the present invention, the mass of the added polycondensation catalyst is one to one-thousandth of the melt mass in the polycondensation reaction.
[0031] In some embodiments of the present invention, the polycondensation catalyst is one or more selected from tetrabutyl titanate, tetraisopropyl titanate, and tetraethoxygermanium.
[0032] Furthermore, the polycondensation catalyst is a combination of tetrabutyl titanate and / or tetraisopropyl titanate and tetraethoxygermanium, wherein the molar ratio of tetrabutyl titanate and / or tetraisopropyl titanate to tetraethoxygermanium is 1.5-4.0:1, for example, it can be 1.5:1, 1.8:1, 2.0:1, 2.2:1, 2.5:1, 2.8:1, 3.0:1, 3.2:1, 3.5:1, 3.8:1, 4.0:1, etc.
[0033] Furthermore, when the polycondensation catalyst is selected from a combination of tetrabutyl titanate and / or tetraisopropyl titanate and tetraethoxygermanium, before addition, the tetrabutyl titanate and / or tetraisopropyl titanate and tetraethoxygermanium are mixed under heating conditions. More preferably, the heating conditions are a controlled temperature of 80-130°C. In practice, it has been unexpectedly found that premixing before addition can achieve better results, such as higher intrinsic viscosity of the polyester and lower DEG content. Further, the inventors of this invention, through research and analysis, believe that this may be due to the interaction between the two after premixing, potentially generating new molecular structures. For example, titanium can form a relatively stable coordination complex with the lone pair electrons of the oxygen atom in tetraethoxygermanium. Simultaneously, this structure may allow ethylene glycol to participate in complexation in the reaction system, ultimately forming a stable complex. During the reaction, the synergistic catalytic effect of titanium and germanium is fully utilized, achieving a balanced catalytic effect, which is beneficial for improving catalytic activity and selectivity, promoting the expansion of the polyester molecular chain, obtaining a larger weight-average molecular weight, and reducing the occurrence of side reactions.
[0034] In some embodiments of the present invention, the polycondensation reaction includes a prepolymerization reaction and a final polymerization reaction. The prepolymerization reaction is controlled to be carried out at a pressure of 800-1200 Pa and a temperature of 260-275 °C, and the final polymerization reaction is controlled to be carried out at a pressure of less than 100 Pa and a temperature of 270-285 °C.
[0035] In some embodiments of the present invention, the heat treatment is controlled to be carried out at a temperature of 100-230°C. Further, the heat treatment is controlled to be carried out at a temperature of 150-220°C. In this invention, the heat treatment setting can further promote the reaction of unreacted materials, which is beneficial to improving the intrinsic viscosity of the polyester, and also has the function of removing impurities, especially when combined with vacuum conditions, which can remove any impurities that may be generated.
[0036] In some embodiments of the invention, the polycondensation reaction is carried out in the presence of a stabilizer. Further, the stabilizer comprises one or more combinations of triphenyl phosphate, trimethyl phosphate, triphenyl phosphite, and dibutyl isobutyl phosphate. According to some specific aspects of the invention, the amount of the stabilizer is from one part per million to one part per ten thousand of the melt mass during the polycondensation reaction.
[0037] In some embodiments of the present invention, after the polycondensation reaction reaches a preset endpoint, the polyester chips are drawn into strips and granulated to obtain polyester chips, which are then heat-treated under vacuum conditions.
[0038] Furthermore, the heat treatment is carried out in a vacuum drum drying oven.
[0039] In some embodiments of the present invention, the heat treatment time is controlled to be 10-60 hours.
[0040] In some embodiments of the present invention, the aforementioned protective atmosphere is formed by introducing nitrogen and / or an inert gas, including helium and / or argon, etc.
[0041] Another technical solution provided by the present invention: a polyester prepared by the above-mentioned method of polyester preparation, wherein the polyester is a high-purity polyester with an intrinsic viscosity of 0.75-0.8 dl / g, a DEG content of less than or equal to 0.5%, an acetaldehyde content of ≤0.2ppm, an Fe content of ≤0.1mg / kg, and an ash content of ≤0.01%.
[0042] Another technical solution provided by this invention is the application of the aforementioned polyester in the preparation of medical materials. Further, the medical materials include, but are not limited to, PET artificial blood vessels for the cardiovascular field, heart valve pads, and sutures for soft tissue repair.
[0043] Due to the application of the above technical solution, the present invention has the following advantages compared with the prior art: This invention addresses the shortcomings of conventional polyethylene terephthalate (PET), such as insufficient intrinsic viscosity and high impurity content, by innovatively providing an improved method for polyester preparation. Based on extensive experimental research, this method first prepares pure small-molecule diethyl terephthalate from small-molecule raw materials, then further disproportionates it to adjust the molecular weight distribution. Simultaneously, dimethyl terephthalate and ethylene glycol are mixed and reacted under normal pressure to further generate various forms of the polyester precursor, such as diethyl terephthalate and oligomers like dimers and trimers. In other words, this invention controls the stepwise preparation of the polyester precursor by controlling ethylene glycol under different conditions. When the reaction products are mixed for polycondensation, different polyester precursors and oligomers with different degrees of polymerization can rapidly complete chain extension, avoiding the problem that a single precursor might struggle to increase molecular weight further after reaching a certain level. Finally, heat treatment achieves solid-phase viscosity enhancement and further impurity removal.
[0044] In particular, the method of the present invention has achieved unexpectedly excellent results in controlling the impurity content in polyester, especially in greatly suppressing impurities such as DEG and acetaldehyde, thereby overcoming the problems of potential degradation and subsequent tissue irritation and mechanical property degradation that may occur when conventional polyester is used in medical materials. Detailed Implementation
[0045] The above-mentioned solution will be further described below with reference to specific embodiments; it should be understood that these embodiments are used to illustrate the basic principles, main features and advantages of the present invention, and the present invention is not limited to the scope of the following embodiments; the implementation conditions used in the embodiments can be further adjusted according to specific requirements, and the implementation conditions not specified are usually the conditions in conventional experiments.
[0046] Unless otherwise specified in the following examples, all raw materials are commercially available or prepared by conventional methods in the art.
[0047] Example 1: This example provides a method for preparing polyester and the polyester produced therefrom. The preparation method includes: (1) Preparation of dihydroxyethyl terephthalate 15 kg of purified terephthalic acid (99.9% purity) and 28 kg of ethylene glycol were mixed into a homogeneous slurry and added to a reactor. The molar ratio of purified terephthalic acid to ethylene glycol was 1:5. After thorough mixing and purging with nitrogen, the temperature was slowly increased while controlling the pressure inside the reactor to not exceed 0.3 MPa for esterification. Esterification was completed when the amount of water discharged from the reactor reached approximately 95% of the theoretical value. The esterification time was approximately 3.5 hours, at which point the reactor temperature reached approximately 257.5 ± 2 °C. After esterification, the mixture was discharged into a prepared tank under nitrogen protection and cooled and crystallized at 5-10 °C for 24 hours. The solid fraction obtained was filtered using an industrial centrifuge and was crude diethyl terephthalate.
[0048] (2) Purification Using ethanol as a solvent, the solution was heated until crude diethyl terephthalate was completely dissolved. Then, 3% (based on the mass of crude diethyl terephthalate) of activated carbon was added for adsorption for 30 minutes. The mixture was then filtered, and the filtrate was cooled to 4°C at a rate of 0.5°C / min to allow for complete crystallization for 12 hours. The resulting crystals were obtained by filtration. This process was repeated twice to obtain high-purity diethyl terephthalate.
[0049] (3) Aggregation (3-1) 7 kg of dimethyl terephthalate and 3.5 kg of ethylene glycol were mixed into a uniform slurry and added to the reactor. 1.79 g of calcium acetate and 1.17 g of sodium acetate were added as catalysts. The mixture was stirred and mixed evenly. After being fully purged with nitrogen, the temperature was slowly increased and the reaction was carried out under normal pressure to ensure that the methanol produced by the reaction could be distilled out smoothly. The reaction was considered to be over when the amount of methanol produced reached 95% of the theoretically calculated value. At this time, the temperature of the reactor was about 235±5℃ and the reaction time was about 3.5 h. (3-2) 3 kg of high-purity diethyl terephthalate and 1.5 kg of ethylene glycol, prepared according to the above method, were heated to 180°C and reacted for 2 hours under nitrogen protection. After the reaction was completed, the mixture was injected into the reaction product of (3-1) above, along with 1.13 g of tetrabutyl titanate and 0.89 g of the stabilizer triphenyl phosphite. After stirring and mixing evenly, a pre-polymerization reaction was carried out. The pressure inside the reactor was slowly and steadily reduced from atmospheric pressure to 1000 Pa. During this process, the temperature was controlled between 265±5°C and the time was controlled at 45 min. After the pre-polymerization reaction was completed, the vacuum inside the reactor was continued to be reduced to less than 100 Pa, and a final polymerization reaction was carried out at a temperature of 277±5°C for 110 min. After the final polymerization reaction was completed, the product was stretched and granulated to obtain polyester chips.
[0050] (4) Solid phase viscosity enhancement The polyester chips were placed in a vacuum drum drying oven and the temperature was set to 200℃. The chips were then thickened under vacuum for 48 hours to obtain high-purity polyester chips. The relevant data are shown in Table 1 below.
[0051] Example 2: This example provides a method for preparing polyester and the polyester produced therefrom. The preparation method includes: (1) Preparation of dihydroxyethyl terephthalate 15 kg of purified terephthalic acid (99.9% purity) and 22.4 kg of ethylene glycol were mixed into a homogeneous slurry and added to a reactor. The molar ratio of purified terephthalic acid to ethylene glycol was 1:4. After thorough mixing and purging with nitrogen, the temperature was slowly increased while controlling the pressure inside the reactor to not exceed 0.3 MPa for esterification. Esterification was completed when the amount of water discharged from the reactor reached approximately 95% of the theoretical value. The esterification time was approximately 3.5 hours, at which point the reactor temperature reached approximately 257.5 ± 2 °C. After esterification, the mixture was discharged into a prepared tank under nitrogen protection and cooled and crystallized at 5-10 °C for 24 hours. The solid fraction obtained was filtered using an industrial centrifuge and was the crude diethyl terephthalate.
[0052] (2) Purification Using ethanol as a solvent, the solution was heated until crude diethyl terephthalate was completely dissolved. Then, 3% (based on the mass of crude diethyl terephthalate) of activated carbon was added for adsorption for 30 minutes. The mixture was then filtered, and the filtrate was cooled to 4°C at a rate of 0.5°C / min to allow for complete crystallization for 12 hours. The resulting crystals were obtained by filtration. This process was repeated twice to obtain high-purity diethyl terephthalate.
[0053] (3) Aggregation (3-1) Mix 6 kg of dimethyl terephthalate and 3 kg of ethylene glycol into a uniform slurry and add it to the reactor. Add 1.54 g of calcium acetate and 1.0 g of sodium acetate as catalysts. Stir and mix evenly. After fully purging with nitrogen, start to slowly heat up and react under normal pressure so that the methanol produced by the reaction can be distilled out smoothly. The reaction is considered to be over when the amount of methanol produced reaches 95% of the theoretical calculation value. At this time, the temperature is about 235±5℃ and the reaction time is about 3.5h. (3-2) 4 kg of high-purity diethyl terephthalate and 2 kg of ethylene glycol prepared according to the above method were heated to 180℃ and reacted for 2 hours under nitrogen protection to ensure complete reaction. After the reaction was completed, the product was injected into the reaction product of (3-1) above, along with 1.13 g of tetrabutyl titanate and 1.2 g of trimethyl phosphate stabilizer. After stirring and mixing evenly, a pre-condensation reaction was carried out. The pressure inside the reactor was slowly and steadily reduced from atmospheric pressure to 1000 Pa. During this process, the temperature was controlled between 265±5℃ and the time was controlled at 45 min. After the pre-condensation reaction was completed, the vacuum inside the reactor was continued to be reduced to less than 100 Pa, and a final condensation reaction was carried out at a temperature of 277±5℃ for 110 min. After the final condensation reaction was completed, the product was stretched and granulated to obtain polyester chips.
[0054] (4) Solid phase viscosity enhancement Polyester chips were placed in a vacuum drum drying oven and subjected to a vacuum condition at 180°C for 30 hours to obtain high-purity polyester chips. The relevant data are shown in Table 1 below.
[0055] Example 3: This example provides a method for preparing polyester and the polyester produced therefrom. The preparation method includes: (1) Preparation of dihydroxyethyl terephthalate 15 kg of purified terephthalic acid (99.9% purity) and 25.2 kg of ethylene glycol were mixed into a homogeneous slurry and added to a reactor. The molar ratio of purified terephthalic acid to ethylene glycol was 1:4.5. After thorough mixing and purging with nitrogen, the temperature was slowly increased while maintaining the pressure inside the reactor below 0.3 MPa for esterification. Esterification was complete when the amount of water discharged reached approximately 95% of the theoretical value, taking about 3.5 hours. At this point, the reactor temperature reached approximately 257.5 ± 2 °C. After esterification, the mixture was discharged into a prepared tank under nitrogen protection and cooled and crystallized at 5-10 °C for 24 hours. The solid fraction obtained was filtered using an industrial centrifuge and was crude diethyl terephthalate.
[0056] (2) Purification Using ethanol as a solvent, the solution was heated until crude diethyl terephthalate was completely dissolved. Then, 3% (based on the mass of crude diethyl terephthalate) of activated carbon was added for adsorption for 30 minutes. The mixture was then filtered, and the filtrate was cooled to 4°C at a rate of 0.5°C / min to allow for complete crystallization for 12 hours. The resulting crystals were obtained by filtration. This process was repeated twice to obtain high-purity diethyl terephthalate.
[0057] (3) Aggregation (3-1) Mix 5 kg of dimethyl terephthalate and 2.5 kg of ethylene glycol into a uniform slurry and add it to the reactor. Add 1.28 g of calcium acetate and 0.83 g of sodium acetate as catalysts. Stir and mix evenly. After fully purging with nitrogen, start to slowly heat up and react under normal pressure so that the methanol produced by the reaction can be distilled out smoothly. The reaction is considered to be over when the amount of methanol produced reaches 95% of the theoretical calculation value. At this time, the temperature of the reactor is about 235±5℃ and the reaction time is about 3.5h. (3-2) 5 kg of high-purity diethyl terephthalate and 2.5 kg of ethylene glycol, prepared according to the above method, were heated to 180°C and reacted for 2 hours under nitrogen protection to ensure complete reaction. After the reaction was completed, the mixture was injected into the reaction product of (3-1) above, along with 1.13 g of tetrabutyl titanate and 0.85 g of trimethyl phosphate stabilizer. After stirring and mixing evenly, a pre-polymerization reaction was carried out. The pressure inside the reactor was slowly and steadily reduced from atmospheric pressure to 1000 Pa. During this process, the temperature was controlled between 265±5°C and the time was controlled at 45 min. After the pre-polymerization reaction was completed, the vacuum inside the reactor was continued to be reduced to less than 100 Pa, and a final polymerization reaction was carried out at a temperature of 277±5°C for 110 min. After the final polymerization reaction was completed, the mixture was stretched and granulated to obtain polyester chips.
[0058] (4) Solid phase viscosity enhancement The polyester chips were placed in a vacuum drum drying oven and the temperature was set to 215℃. The chips were then thickened under vacuum for 36 hours to obtain high-purity polyester chips. The relevant data are shown in Table 1 below.
[0059] Example 4: This example provides a method for preparing polyester and the polyester produced therefrom. The preparation method includes: (1) Preparation of dihydroxyethyl terephthalate 15 kg of purified terephthalic acid (99.9% purity) and 22.4 kg of ethylene glycol were mixed into a homogeneous slurry and added to a reactor. The molar ratio of purified terephthalic acid to ethylene glycol was 1:4. After thorough mixing and purging with nitrogen, the temperature was slowly increased while controlling the pressure inside the reactor to not exceed 0.3 MPa for esterification. Esterification was completed when the amount of water discharged from the reactor reached approximately 95% of the theoretical value. The esterification time was approximately 3.5 hours, at which point the reactor temperature reached approximately 257.5 ± 2 °C. After esterification, the mixture was discharged into a prepared tank under nitrogen protection and cooled and crystallized at 5-10 °C for 24 hours. The solid fraction obtained was filtered using an industrial centrifuge and was the crude diethyl terephthalate.
[0060] (2) Purification Using ethanol as a solvent, the solution was heated until crude diethyl terephthalate was completely dissolved. Then, 3% (based on the mass of crude diethyl terephthalate) of activated carbon was added for adsorption for 30 minutes. The mixture was then filtered, and the filtrate was cooled to 4°C at a rate of 0.5°C / min to allow for complete crystallization for 12 hours. The resulting crystals were obtained by filtration. This process was repeated twice to obtain high-purity diethyl terephthalate.
[0061] (3) Aggregation (3-1) 4 kg of dimethyl terephthalate and 2 kg of ethylene glycol were mixed into a uniform slurry and added to the reactor. 1.02 g of calcium acetate and 0.67 g of sodium acetate were added as catalysts. The mixture was stirred and mixed evenly. After being fully purged with nitrogen, the temperature was slowly increased and the reaction was carried out under normal pressure to ensure that the methanol produced by the reaction could be distilled out smoothly. The reaction was considered to be over when the amount of methanol produced reached 95% of the theoretically calculated value. At this time, the temperature of the reactor was about 235±5℃ and the reaction time was about 3.5 h. (3-2) 6 kg of high-purity diethyl terephthalate and 3 kg of ethylene glycol, prepared according to the above method, were heated to 180℃ and reacted for 2 hours under nitrogen protection to ensure complete reaction. After the reaction was completed, the product was injected into the reaction product of (3-1) above, along with 1.13 g of tetrabutyl titanate and 1.2 g of trimethyl phosphate stabilizer. After stirring and mixing evenly, a pre-condensation reaction was carried out. The pressure inside the reactor was slowly and steadily reduced from atmospheric pressure to 1000 Pa. During this process, the temperature was controlled between 265±5℃ and the time was controlled at 45 min. After the pre-condensation reaction was completed, the vacuum inside the reactor was continued to be reduced to less than 100 Pa, and a final condensation reaction was carried out at a temperature of 277±5℃ for 110 min. After the final condensation reaction was completed, the product was stretched and granulated to obtain polyester chips.
[0062] (4) Solid phase viscosity enhancement The polyester chips were placed in a vacuum drum drying oven and the temperature was set to 215℃. The chips were then thickened under vacuum for 48 hours to obtain high-purity polyester chips. The relevant data are shown in Table 1 below.
[0063] Example 5: This example provides a method for preparing polyester and the polyester produced therefrom. The preparation method includes: (1) Preparation of dihydroxyethyl terephthalate 15 kg of purified terephthalic acid (99.9% purity) and 22.4 kg of ethylene glycol were mixed into a homogeneous slurry and added to a reactor. The molar ratio of purified terephthalic acid to ethylene glycol was 1:4. After thorough mixing and purging with nitrogen, the temperature was slowly increased while controlling the pressure inside the reactor to not exceed 0.3 MPa for esterification. Esterification was completed when the amount of water discharged from the reactor reached approximately 95% of the theoretical value. The esterification time was approximately 3.5 hours, at which point the reactor temperature reached approximately 257.5 ± 2 °C. After esterification, the mixture was discharged into a prepared tank under nitrogen protection and cooled and crystallized at 5-10 °C for 24 hours. The solid fraction obtained was filtered using an industrial centrifuge and was the crude diethyl terephthalate.
[0064] (2) Purification Using ethanol as a solvent, the solution was heated until crude diethyl terephthalate was completely dissolved. Then, 3% (based on the mass of crude diethyl terephthalate) of activated carbon was added for adsorption for 30 minutes. The mixture was then filtered, and the filtrate was cooled to 4°C at a rate of 0.5°C / min to allow for complete crystallization for 12 hours. The resulting crystals were obtained by filtration. This process was repeated twice to obtain high-purity diethyl terephthalate.
[0065] (3) Aggregation (3-1) Mix 3 kg of dimethyl terephthalate and 1.5 kg of ethylene glycol into a uniform slurry and add it to the reactor. Add 0.77 g of calcium acetate and 0.59 g of sodium acetate as catalysts. Stir and mix evenly. After fully purging with nitrogen, start to slowly heat up and react under normal pressure so that the methanol produced by the reaction can be distilled out smoothly. The reaction is considered to be over when the amount of methanol produced reaches 95% of the theoretical calculation value. At this time, the temperature of the reactor is about 235±5℃ and the reaction time is about 3.5h.
[0066] (3-2) 7 kg of high-purity diethyl terephthalate and 3.5 kg of ethylene glycol, prepared according to the above method, were heated to 180℃ and reacted for 2 hours under nitrogen protection to ensure complete reaction. After the reaction was completed, the product was injected into the reaction product of (3-1) above, and 1.13 g of tetrabutyl titanate and 0.85 g of trimethyl phosphate stabilizer were added. After stirring and mixing evenly, a pre-condensation reaction was carried out. The pressure inside the reactor was slowly and steadily reduced from atmospheric pressure to 1000 Pa. During this process, the temperature was controlled between 265±5℃ and the time was controlled at 45 min. After the pre-condensation reaction was completed, the vacuum inside the reactor was continued to be reduced to less than 100 Pa, and a final condensation reaction was carried out at a temperature of 277±5℃ for 110 min. After the final condensation reaction was completed, the product was stretched and granulated to obtain polyester chips. (4) Solid phase viscosity enhancement The polyester chips were placed in a vacuum drum drying oven and the temperature was set to 220℃. The chips were then thickened under vacuum for 18 hours to obtain high-purity polyester chips. The relevant data are shown in Table 1 below.
[0067] Example 6: This example provides a method for preparing a polyester and the polyester produced therefrom. The preparation method is basically the same as in Example 2, except that the catalyst is prepared using the following method: tetraisopropyl titanate and tetraethoxygermanium are mixed at a molar ratio of 2:1 at 120 degrees Celsius for 2 hours to obtain the catalyst product. Relevant index data are shown in Table 1 below.
[0068] Example 7: This example provides a method for preparing a polyester and the polyester produced therefrom. The preparation method is basically the same as in Example 2, except that the catalyst used is an equal mass of tetraisopropyl titanate. Relevant index data are shown in Table 1 below.
[0069] Example 8: This example provides a method for preparing a polyester and the polyester produced therefrom. The preparation method is basically the same as in Example 2, except that the catalyst used is an equal mass of tetraethoxygermanium. Relevant index data are shown in Table 1 below.
[0070] Example 9: This example provides a method for preparing a polyester and the polyester produced therefrom. The preparation method is basically the same as in Example 2, except that the catalyst used is 0.9 g of tetraisopropyl titanate and 0.4 g of tetraethoxygermanium. Relevant data are shown in Table 1 below.
[0071] Comparative Example 1: Purified terephthalic acid, ethylene glycol, and antimony glycol catalyst were added to a reactor for reaction. The molar ratio of purified terephthalic acid to ethylene glycol was 1:1.35. The amount of antimony glycol catalyst, calculated as antimony element, was 210 ppm of the total polymer. After stirring and mixing thoroughly, the mixture was completely purged with nitrogen. The temperature was then slowly increased while controlling the pressure inside the reactor to not exceed 0.3 MPa for esterification. Esterification was completed when the amount of water discharged from the esterification reached approximately 95% of the theoretical value. The esterification time was approximately 3.5 hours, at which point the reactor temperature reached approximately 257.5 ± 2 °C. After esterification, a pre-condensation reaction was carried out. A vacuum was drawn to slowly and steadily reduce the pressure inside the reactor from atmospheric pressure to 1000 Pa. During this process, the temperature was controlled between 265 ± 5 °C and the time was controlled to 40 minutes. After the pre-polymerization reaction is complete, vacuum is continued in the reactor to ensure the vacuum level is less than 100 Pa, and the final polymerization reaction is carried out at a temperature of 275±5℃ for 110 min. After the polymerization reaction is complete, the product is stretched and granulated to obtain polyester chips. The polyester chips are then placed in a vacuum drum drying oven and subjected to a vacuum condition at 180℃ for 30 hours to thicken the product, yielding the processed polyester chips. Relevant data are shown in Table 1 below.
[0072] Comparative Example 2: This example provides a method for preparing polyester and the polyester produced therefrom. The preparation method includes: (1) Preparation of dihydroxyethyl terephthalate 15 kg of purified terephthalic acid (99.9% purity) and 22.4 kg of ethylene glycol were mixed into a homogeneous slurry and added to a reactor. The molar ratio of purified terephthalic acid to ethylene glycol was 1:4. After thorough mixing and purging with nitrogen, the temperature was slowly increased while controlling the pressure inside the reactor to not exceed 0.3 MPa for esterification. Esterification was completed when the amount of water discharged from the reactor reached approximately 95% of the theoretical value. The esterification time was approximately 3.5 hours, at which point the reactor temperature reached approximately 257.5 ± 2 °C. After esterification, the mixture was discharged into a prepared tank under nitrogen protection and cooled and crystallized at 5-10 °C for 24 hours. The solid fraction obtained was filtered using an industrial centrifuge and was the crude diethyl terephthalate.
[0073] (2) Purification Using ethanol as a solvent, the solution was heated until crude diethyl terephthalate was completely dissolved. Then, 3% (based on the mass of crude diethyl terephthalate) of activated carbon was added for adsorption for 30 minutes. The mixture was then filtered, and the filtrate was allowed to cool to 4°C at a rate of 0.5°C / min for 12 hours to fully crystallize. The resulting crystals were obtained by filtration. This process was repeated twice to obtain high-purity diethyl terephthalate.
[0074] (3) Aggregation 4 kg of high-purity diethyl terephthalate and 2 kg of ethylene glycol, prepared according to the above method, were heated to 180°C and reacted for 2 hours under nitrogen protection to ensure complete reaction. After the reaction was completed, 1.13 g of tetrabutyl titanate and 1.2 g of trimethyl phosphate stabilizer were added, and the mixture was stirred and mixed evenly before a pre-polymerization reaction was carried out. The pressure inside the reactor was slowly and steadily reduced from atmospheric pressure to 1000 Pa during this process, with the temperature controlled between 265±5°C and the time controlled at 45 min. After the pre-polymerization reaction was completed, the vacuum inside the reactor was continued to be reduced to less than 100 Pa, and the final polymerization reaction was carried out at a temperature of 277±5°C for 110 min. After the final polymerization reaction was completed, the product was stretched and granulated to obtain polyester chips. (4) Solid phase viscosity enhancement The polyester chips were placed in a vacuum drum drying oven and the temperature was set to 180℃. The adhesive was thickened under vacuum for 30 hours to obtain the treated polyester chips. The relevant index data are shown in Table 1 below.
[0075] Comparative Example 3: This example provides a method for preparing polyester and the polyester produced therefrom. The preparation method includes: (1) Preparation of dihydroxyethyl terephthalate 15 kg of purified terephthalic acid (99.9% purity) and 22.4 kg of ethylene glycol were mixed into a homogeneous slurry and added to a reactor. The molar ratio of purified terephthalic acid to ethylene glycol was 1:4. After thorough mixing and purging with nitrogen, the temperature was slowly increased while controlling the pressure inside the reactor to not exceed 0.3 MPa for esterification. Esterification was completed when the amount of water discharged from the reactor reached approximately 95% of the theoretical value. The esterification time was approximately 3.5 hours, at which point the reactor temperature reached approximately 257.5 ± 2 °C. After esterification, the mixture was discharged into a prepared tank under nitrogen protection and cooled and crystallized at 5-10 °C for 24 hours. The solid fraction obtained was filtered using an industrial centrifuge and was the crude diethyl terephthalate.
[0076] (2) Purification Using ethanol as a solvent, the solution was heated until crude diethyl terephthalate was completely dissolved. Then, 3% (based on the mass of crude diethyl terephthalate) of activated carbon was added for adsorption for 30 minutes. The mixture was then filtered, and the filtrate was allowed to cool to 4°C at a rate of 0.5°C / min for 12 hours to fully crystallize. The resulting crystals were obtained by filtration. This process was repeated twice to obtain high-purity diethyl terephthalate.
[0077] (3) Aggregation (3-1) Mix 6 kg of dimethyl terephthalate and 3 kg of ethylene glycol into a uniform slurry and add it to the reactor. Add 1.54 g of calcium acetate and 1.0 g of sodium acetate as catalysts. Stir and mix evenly. After fully purging with nitrogen, start to slowly heat up and react under normal pressure so that the methanol produced by the reaction can be distilled out smoothly. The reaction is considered to be over when the amount of methanol produced reaches 95% of the theoretical calculation value. At this time, the temperature of the reactor is about 235±5℃ and the reaction time is about 3.5h. (3-2) 4 kg of high-purity diethyl terephthalate and 2 kg of ethylene glycol prepared according to the above method were injected into the reaction product of (3-1), along with 1.13 g of tetrabutyl titanate and 1.2 g of trimethyl phosphate stabilizer. After stirring and mixing evenly, a pre-polymerization reaction was carried out. The pressure inside the reactor was slowly and steadily reduced from atmospheric pressure to 1000 Pa under vacuum. The temperature was controlled between 265 ± 5 °C, and the time was controlled at 45 min. After the pre-polymerization reaction was completed, vacuum was continued to reduce the vacuum inside the reactor to less than 100 Pa, and a final polymerization reaction was carried out at a temperature of 277 ± 5 °C for 110 min. After the final polymerization reaction was completed, the product was stretched and granulated to obtain polyester chips.
[0078] (4) Solid phase viscosity enhancement The polyester chips were placed in a vacuum drum drying oven and the temperature was set to 180℃. The adhesive was thickened under vacuum for 30 hours to obtain the treated polyester chips. The relevant index data are shown in Table 1 below.
[0079] Table 1
[0080] The testing standards for intrinsic viscosity, DEG, Fe, ash content, and color value in the above data refer to GB / T14190-2017, and the testing standard for acetaldehyde refers to GB / T17931-2018. Note: In this invention, the DEG content (%) includes free DEG and DEG functional groups involved in polyester bonding.
[0081] As shown in Table 1, the polyester of this invention achieves high intrinsic viscosity while maintaining high cleanliness, with DEG content below 0.5% and acetaldehyde content below 0.2 ppm. It also exhibits superior color value, better transparency, and less degradation. In contrast, conventional polyesters not only have high impurity content but also lower intrinsic viscosity and lower L-value. While the polyester prepared using a single high-purity diethyl terephthalate process achieves good cleanliness, its intrinsic viscosity and b-value are not ideal. Comparative Example 3 lacks a disproportionation step, resulting in relatively good cleanliness, but its intrinsic viscosity and b-value are also unsatisfactory. None of these methods can simultaneously achieve high intrinsic viscosity, excellent color value, and cleanliness, resulting in a trade-off between these aspects.
[0082] In summary, the polyester prepared by this invention has an intrinsic viscosity of 0.75-0.8 dl / g, a DEG content of less than or equal to 0.5%, an acetaldehyde content of ≤0.2 ppm, an Fe content of ≤0.1 mg / kg, and an ash content of ≤0.01%. It can be used as a high-purity polyester, with good chemical stability, good toughness, good compatibility, and no toxic side effects. It can be used to produce medical catheters such as infusion tubes and artificial blood vessels, ensuring the safety and stability of medical products during use.
[0083] As used throughout the specification and claims, the term "comprising" is an open-ended term and should be interpreted as "comprising but not limited to." "Substantially" means that within an acceptable margin of error, those skilled in the art can solve the technical problem and substantially achieve the technical effect. It should also be noted that the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a product or system comprising a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a product or system. Without further limitations, an element defined by the phrase "comprising one" does not exclude the presence of other identical elements in the product or system comprising said element.
[0084] The above embodiments are only for illustrating the technical concept and features of the present invention, and are intended to enable those skilled in the art to understand the content of the present invention and implement it accordingly. They should not be construed as limiting the scope of protection of the present invention. All equivalent changes or modifications made in accordance with the spirit and essence of the present invention should be covered within the scope of protection of the present invention.
[0085] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
Claims
1. A method for preparing polyester, characterized in that, The preparation method includes: (1) Terephthalic acid and ethylene glycol undergo an esterification reaction. After the reaction is completed, the mixture is separated and purified to obtain purified dihydroxyethyl terephthalate. The purified dihydroxyethyl terephthalate was subjected to a disproportionation reaction with ethylene glycol to obtain the first reaction mixture; Dimethyl terephthalate and ethylene glycol are mixed and reacted under normal pressure. After the reaction is completed, a second reaction mixture is obtained. (2) The first reaction mixture and the second reaction mixture are subjected to polycondensation reaction in the presence of a polycondensation catalyst. After the reaction is completed, the polycondensation product is heat-treated under vacuum to obtain polyester.
2. The method for preparing polyester according to claim 1, characterized in that, In the esterification reaction, the molar amount of ethylene glycol added is more than twice the molar amount of terephthalic acid added; and / or, in the mixed reaction, the molar amount of ethylene glycol added is 1.1-2 times the molar amount of dimethyl terephthalate added; and / or, the esterification reaction is controlled at a temperature of 230-260°C and a pressure of 0.005-0.32 MPa.
3. The method for preparing polyester according to claim 1, characterized in that, In the esterification reaction, the molar amount of ethylene glycol added is 2-6 times the molar amount of terephthalic acid added.
4. The method for preparing polyester according to claim 1, characterized in that, The method for preparing the purified dihydroxyethyl terephthalate includes: Terephthalic acid and ethylene glycol undergo an esterification reaction. The reaction ends when the amount of water discharged reaches more than 95% of the theoretically calculated value. Then, under a protective atmosphere, the reactants are discharged into a container, cooled and crystallized, and filtered to obtain crude dihydroxyethyl terephthalate. The crude diethyl terephthalate was dissolved in a solvent under heating conditions, activated carbon was added, and the mixture was filtered. The filtrate was cooled and crystallized, then filtered again. This process was selectively repeated multiple times to obtain purified diethyl terephthalate.
5. The method for preparing polyester according to claim 4, characterized in that, The solvent is selected from one or more combinations of water, methanol, ethanol, n-propanol, formic acid, and acetic acid.
6. The method for preparing polyester according to claim 4, characterized in that, The amount of activated carbon added is 0.5%-5% of the amount of crude bis(hydroxyethyl) terephthalate added.
7. The method for preparing polyester according to claim 4, characterized in that, The crystallization temperature for cooling crystallization is 1-10℃, and the cooling rate is 0.1-1℃ / min.
8. The method for preparing polyester according to claim 1, characterized in that, In the disproportionation reaction, the molar ratio of the purified diethyl terephthalate to the ethylene glycol is 1:0.5-5; and / or, The disproportionation reaction is controlled to occur under a protective atmosphere at 150-180°C; and / or, The mixing reaction is controlled to proceed in the presence of a catalyst, wherein the mass of the catalyst fed is one part per million to one part per thousand of the mass of the dimethyl terephthalate fed; and / or, The mixing reaction is controlled to be carried out at 180-240°C; and / or, The endpoint of the mixed reaction is controlled when the amount of methanol produced reaches more than 90% of the theoretically calculated value.
9. The method for preparing polyester according to claim 1, characterized in that, The mixed reaction is controlled to proceed in the presence of a catalyst, which is a combination of one, two or more selected from alkali metal acetates and transition metal acetates.
10. The method for preparing polyester according to claim 9, characterized in that, The catalyst is composed of alkali metal acetate and transition metal acetate.
11. The method for preparing polyester according to claim 10, characterized in that, The mass ratio of the alkali metal acetate to the transition metal acetate is 1:1.2-1.
6.
12. The method for preparing polyester according to claim 1, characterized in that, The preparation method further includes adjusting the feeding ratio of the first reaction mixture to the second reaction mixture by controlling the feeding amount of the purified dihydroxyethyl terephthalate and the feeding amount of dimethyl terephthalate.
13. The method for preparing polyester according to claim 12, characterized in that, With the total amount of dimethyl terephthalate and the purified diethyl terephthalate being 100%, the dimethyl terephthalate accounts for 30%-70%, and the purified diethyl terephthalate accounts for 30%-70%.
14. The method for preparing polyester according to claim 13, characterized in that, With the total amount of dimethyl terephthalate and the purified diethyl terephthalate being 100%, the dimethyl terephthalate accounts for 50%-70%, and the purified diethyl terephthalate accounts for 30%-50%.
15. The method for preparing polyester according to claim 1, characterized in that, The polycondensation catalyst is a titanium catalyst, a germanium catalyst, or a combination of both.
16. The method for preparing polyester according to claim 15, characterized in that, The titanium catalyst comprises titanate, and the germanium catalyst comprises organic germanium.
17. The method for preparing polyester according to claim 1, characterized in that, The mass of the added polycondensation catalyst is one to one-millionth of the melt mass in the polycondensation reaction.
18. The method for preparing polyester according to claim 1 or 15, characterized in that, The polycondensation catalyst is selected from one or more of tetrabutyl titanate, tetraisopropyl titanate, and tetraethoxygermanium.
19. The method for preparing polyester according to claim 1, characterized in that, The polycondensation catalyst is a combination of tetrabutyl titanate and / or tetraisopropyl titanate and tetraethoxygermanium, wherein the molar ratio of tetrabutyl titanate and / or tetraisopropyl titanate to tetraethoxygermanium is 1.5-4.0:
1.
20. The method for preparing polyester according to claim 19, characterized in that, When the polycondensation catalyst is selected from a combination of tetrabutyl titanate and / or tetraisopropyl titanate and tetraethoxygermanium, the tetrabutyl titanate and / or tetraisopropyl titanate and tetraethoxygermanium are mixed under heating conditions before addition.
21. The method for preparing polyester according to claim 20, characterized in that, The heating conditions are to control the temperature between 80-130℃.
22. The method for preparing polyester according to claim 1, characterized in that, The polycondensation reaction includes a prepolymerization reaction and a final polymerization reaction. The prepolymerization reaction is controlled to be carried out at a pressure of 800-1200 Pa and a temperature of 260-275 °C. The final polymerization reaction is controlled to be carried out at a pressure below 100 Pa and a temperature of 270-285 °C. And / or, the heat treatment is controlled to be carried out at a temperature of 100-230 °C.
23. A polyester made by a method for preparing the polyester according to any one of claims 1-22.
24. The polyester according to claim 23, characterized in that, The polyester is a high-cleanliness polyester with an intrinsic viscosity of 0.75-0.8 dl / g, a DEG content of less than or equal to 0.5%, an acetaldehyde content of ≤0.2ppm, an Fe content of ≤0.1mg / kg, and an ash content of ≤0.01%.
25. The use of the polyester of claim 23 or 24 in the preparation of medical materials.
Citation Information
Patent Citations
Method for preparing PET by using terephthalic acid in alkali reduction wastewater
CN110862520A
Biodegradable terephthalate polyester-poly(phosphate) polymers, compositions, articles,and method for making and using the same
CN1256700A